1984
DOI: 10.3109/00365548409087131
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus Infection and Disease in Sweden and the Relative Importance of Primary and Secondary Maternal Infections: Preliminary Findings from a Prospective Study

Abstract: In a prospective Swedish study started in 1977 and still in progress 10 328 newborn infants in an urban district were investigated for cytomegalovirus (CMV) excretion in the urine by the virus isolation test. Congenital infection was found in 50 cases (0.5%). Of 47 infected infants with known clinical status at birth 9 (19%) had hepatomegaly, splenomegaly, jaundice and/or petechiae. The symptoms were moderate or mild. Of the infants followed up, 2 (25%) of 8 neonatally symptomatic ones and 3 (9%) of 35 asympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…Similar to the findings from studies conducted in populations with different CMV seroprevalence rates in the U.S. and Europe, the results of our study indicated that symptomatic infants were significantly more likely to develop SNHL than those with asymptomatic infection 1–3 . Thus, the presence of CMV-related symptoms at birth is a strong predictor of hearing loss, even in populations with high maternal CMV seroprevalence rate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the findings from studies conducted in populations with different CMV seroprevalence rates in the U.S. and Europe, the results of our study indicated that symptomatic infants were significantly more likely to develop SNHL than those with asymptomatic infection 1–3 . Thus, the presence of CMV-related symptoms at birth is a strong predictor of hearing loss, even in populations with high maternal CMV seroprevalence rate.…”
Section: Discussionsupporting
confidence: 90%
“…Population based studies in Sweden 1 , Canada 2 and USA 3, 4 have reported that between 9.3% and 17% of infants with congenital CMV infection will have sensorineural hearing loss (SNHL). The rates of SNHL reported by these studies ranged between 22%–41% in children with clinically apparent or symptomatic infection and between 6–16% in those with subclinical or asymptomatic infection.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Congenital infection may result from either primary or recurrent (due to reactivation of reinfection) infection in the mother. Although serious handicaps are more likely after primary rather than recurrent infection,219 neurological damage and bilateral hearing loss have occasionally been reported in children whose mothers undoubtedly had recurrent infection.2720 More data are required from large prospective studies before the risk associated with recurrent infection can be determined.…”
Section: Health and Efficiencymentioning
confidence: 99%
“…Seroprevalence of CMV in women of childbearing age in the UK is around 50%, but varies by ethnicity, social class and parity 1. Congenital CMV infection can result from recurrent (reactivation of latent infection or reinfection with a new strain) or primary maternal infection in pregnancy 2 3. The birth prevalence of congenital CMV in resource-rich countries varies according to maternal seroprevalence, and in the UK is estimated to be around 3 per 1000 4 5.…”
Section: Introductionmentioning
confidence: 99%